Expanding Horizons: Contribution of an Online Community in the Professional Learning of Teachers in Pakistan: Asma Khan (PJDOL, 2023)
This qualitative study explored the role of an online community for English teachers, English Companion Ning (ECN), in the professional learning of university English teachers in Pakistan. Data were collected through in-depth interviews, weekly guided tours of the ECN, field notes, ECN artifacts/documents and researcher memos. Charmaz (2014) constructivist grounded theory approach was used to analyze the data. Findings indicated that the Pakistani teachers analyzed and discussed their teaching related concerns with teachers globallythrough the platform of ECN.